COVID-19 and thermoregulation-related problems: Practical recommendations. Issue 1 (2nd January 2021) - Daanen, Hein; Bose-O'Reilly, Stephan; Brearley, Matt; Flouris, D. Andreas; Gerrett, Nicola M.; Huynen, Maud; Jones, Hunter M.; Lee, Jason Kai Wei; Morris, Nathan; Norton, Ian; Nybo, Lars; Oppermann, Elspeth; et al.
ABSTRACT: The COVID-19 pandemic started in the cold months of the year 2020 in the Northern hemisphere. Concerns were raised that the hot season may lead to additional problems as some typical interventions to prevent heat-related illness could potentially conflict with precautions to reduce coronavirus transmission. Therefore, an international research team organized by the Global Health Heat Information Network generated an inventory of the specific concerns about this nexus and began to address the issues. Three key thermal and covid-19 related topics were highlighted: 1) For the general public, going to public cool areas in the hot season interferes with the recommendation to stay at home to reduce the spread of the virus. Conflicting advice makes it necessary to revise national heat plans and alert policymakers of this forecasted issue. 2) For medical personnel working in hot conditions, heat strain is exacerbated due to a reduction in heat loss from wearing personal protective equipment to prevent contamination. To avoid heat-related injuries, medical personnel are recommended to precool and to minimize the increase in body core temperature using adopted work/rest schedules, specific clothing systems, and by drinking cold fluids. 3) Fever, one of the main symptoms of COVID-19, may be difficult to distinguish from heat-induced hyperthermia and a resting period may be necessary prior to measurement to avoid misinterpretation. In summary, heat in combination with the COVID-19 pandemic leads to additional problems; the impact of which can be reduced by revising heat plans and implementing special measures attentive to these compound risks.